Proceedings of the 1st International Conference on Language, Literature, and Arts Education (ICLLAE 2019) 2020
DOI: 10.2991/assehr.k.200804.063
|View full text |Cite
|
Sign up to set email alerts
|

Deconstruction-Critical Thinking: Alternative Learning Model of Literature Appreciation in Industrial Revolution 4.0

Abstract: Deconstruction-critical thinking is an effort to develop a creative Literature Appreciation learning model. All deconstruction is critical, but everyone's critical is different and not all perfect. This model is the result of Derrida's deconstruction fiction with critical thinking of the Facione Model. Deconstruction-critical is carried out to find something new that is contradictory by dismantling text based on language instability, phonocentrism-logocentrism, and metaphors, it is necessary to bring up new me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…So that students will be able to compete with the era of the industrial revolution 4.0. This is in line with research conducted by [41] who revealed that critical thinking and daring to express opinions are one of the skills that must be possessed in the era of the industrial revolution.…”
Section: Competence In Future Strategiessupporting
confidence: 89%
“…So that students will be able to compete with the era of the industrial revolution 4.0. This is in line with research conducted by [41] who revealed that critical thinking and daring to express opinions are one of the skills that must be possessed in the era of the industrial revolution.…”
Section: Competence In Future Strategiessupporting
confidence: 89%